Structural Gravity and the Gains from Trade under Imperfect Competition - Benedikt Heid; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2020)
We extend structural gravity models of bilateral trade flows to oligopolistic competition. We show that conventional gravity estimates do not only reflect trade costs but also market power. Our simple estimation procedure generalizes the standard gravity model and disentangles exogenous trade frictions and endogenous market power distortions. We use our estimated model to counterfactually increase trade costs by abolishing the European Single Market. We find that domestic firms' markups in EU member countries increase by 2 to 6 percent. Importantly, welfare effects of trade liberalization are much more pronounced due to the change in competition among domestic and foreign firms.
Keywords: F10; F12; 330; trade; structural gravity; imperfect competition; market power